2020
DOI: 10.1002/agj2.20338
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term fertilization effects on crop yield and desalinized soil properties

Abstract: The effects of long-term fertilization on crop yield and soil property in maize (Zea mays L.)-wheat (Triticum aestivum L.) rotation of desalinized soils are limited. A long-term fertilization experiment was established in 1996 to compare the impact of single and mixed mineral (NPK), and manure fertilization on crop yields and soil properties. The long-term application of manure (OF) and N fertilizer significantly increased crop yields by the 129 and 42% of yield increase, respectively, over other chemical fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…This characteristic is beneficial to the nutrient supply and yield improvement of crops. Related studies have also shown the effect on production increase [39][40][41][42]. However, this study indicated that the contribution of organic materials to PC was small, although the total SOC s increased.…”
Section: Effects On Soc Stability Derived From Different Nss Practicesmentioning
confidence: 54%
“…This characteristic is beneficial to the nutrient supply and yield improvement of crops. Related studies have also shown the effect on production increase [39][40][41][42]. However, this study indicated that the contribution of organic materials to PC was small, although the total SOC s increased.…”
Section: Effects On Soc Stability Derived From Different Nss Practicesmentioning
confidence: 54%
“…Similarly, Yang et al (2014) reported that combinations of organic and inorganic nitrogen are likely to increase achievable yields and improve soil fertility with the wheatmaize system. This might be due to all organic fertilizers being used as base fertilizers in the wheat season, all chemical fertilizers being used in maize planting, and organic fertilizer incorporation into the soil, which increased soil OM contents, soil water availability, and aeration (Choudhary et al, 2018;Li et al, 2020). Welbaum et al 2004) and Li et al (2012) reported that when organic fertilizers incorporation can delay the senescence rate of crop roots and leaves, prolong the photosynthetic time of crops, increase the grain quality of ears by prolonging the grain filling time, and finally increase the yield.…”
Section: Effect Of Organic Fertilizer Incorporation On Crop Yieldsmentioning
confidence: 99%
“…Soil fertility refers to the capacity for soil to offer different nutrients for crop growth, significantly affecting crop yield [1,2]. Scientific and reasonable evaluation of soil fertility can provide a reference for land-use planning and fertilizer prescriptions, guiding agricultural production [3].…”
Section: Introductionmentioning
confidence: 99%